PENGARUH PENGUNGAPAN CSR, STRUKTUR KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN FOOD AND BEVERAGES PERIODE 2015-2019 - Hastuti, Aprilia Dwi (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
ABSTRACK This study aims to determine the effect of CSR disclosure, managerial share ownership, institutional share ownership, and company size on financial performance in the Food and Beverages sub-sector companies for the period 2015- 2019. Based on the purposive sampling method, the sample obtained is 11 companies, so the data obtained is 55 observational data. The financial performance in this study was measured using Return on Equity (ROE), while the statistical analysis used in this study was multiple linear regression analysis using the Statistical Product and Service Solutions (SPSS) program version 18. The results showed that the variable CSR disclosure, managerial share ownership and company size partially do not affect the financial performance of the Food and Beverages subsector companies, while institutional share ownership variables partially have a negative significant effect on the financial performance of the Food and Beverages subsector companies. Keywords: CSR Disclosure, Managerial Share Ownership, Institusional Share Ownership, Company Size, Financial Performance